Angiotensin-Converting Enzyme Inhibitor Does Not Suppress Renal Angiotensin II Levels in Angiotensin I-Infused Rats - Keisuke Ohnishi; Miki Murase; Daisuke Nakano; Nicolas Pelisch; Hirofumi Hitomi; Hiroyuki Kobori; Satoshi Morimoto; Hirohito Mori; Tsutomu Masaki; Koji Ohmori; Masakazu Kohno; Atsuhiro Ichihara; et al. (Elsevier, 2013)
Angiotensin II (Ang II) infusion into rats elevates local angiotensin II levels through an AT1 receptor-dependent pathway in the kidney. We examined whether treatment with an angiotensin-converting enzyme (ACE) inhibitor, temocapril, or an AT1-receptor blocker, olmesartan, prevented elevation of Ang II levels in the kidney of angiotensin I (Ang I)-infused rats. Rats were infused with Ang I (100 ng/min) and treated with temocapril (30 mg/kg per day, n = 10) or olmesartan (10 mg/kg per day, n = 9) for 4 weeks. Ang I infusion significantly elevated blood pressure compared with vehicle-infused rats (n = 6). Treatment with temocapril or olmesartan suppressed Ang I-induced hypertension. Temocapril suppressed both plasma and renal ACE activity. Ang I infusion increased Ang II content in the kidney. Interestingly, temocapril failed to reduce the level of Ang II in the kidney, while olmesartan markedly suppressed an increase in renal Ang II levels. These results suggest a limitation of temocapril and a benefit of olmesartan to inhibit the renal renin-angiotensin system and suggest the possible existence of an ACE inhibitor- insensitive pathway that increases Ang II levels in rat kidney. Keywords:: angiotensin-converting enzyme (ACE) inhibitor, angiotensin II, kidney